The AfCFTA and African trade: An introduction to the special issue - Hippolyte Fofack; Andrew Mold (Journal of African Trade, 2021)
The agreement establishing the African Continental Free Trade Area (AfCFTA) has been attracting a great deal of attention in academic and policy circles, as well as within the international development community. The growing interest in the AfCFTA partly reflects the fact that the African continent is bucking a global trend toward greater protectionism. But it also represents a break with the past on a continent where market fragmentation has emerged as a major constraint to growth and economic development. The AfCFTA offers the opportunity to accelerate the transformation of African economies to boost intra-African trade and enhance integration of the region into the global economy. This paper introduces the Special Issue on 'The AfCFTA and African Trade'. It provides an overview of the existing literature, explores the implications of the landmark agreement for African trade and economic development, and highlights some of the potential challenges associated with its operationalization.
Keywords: 330; AfCFTA; African trade; regional integration; intra-African trade; international economics